The Leadership of Tuan Guru H. Abdurrasyid in Initiating the Birth of Arabische School and Early Pesantren Rasyidiyah Khalidiyah Amuntai - Malisi, M. Ali Sibram; Hartati, Zainap; Rizki, Satria; Rahmawati, Laila (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study aims to explore the role of historiography in initiating the birth of the Arbische School (Pesantren Rasyidiyah Khalidiyah Awal) by examining the process and meaning behind history-making related to the pioneer leadership and influence of Tuan Guru H. Abdurrasyid in the religious community. Historical/historiographic research (descriptive qualitative) uses primary data sources, namely information from direct observation of the research location by observation and oral history interviews. The secondary source is data from documentation or literature studies to complete primary data. Data collection is carried out through field research. The results showed that the character of Mr. Guru H. Abdurrasyid as the first alumnus of al-Azhar Cairo Egypt at the Khalidiyah Rashidiya Islamic Boarding School is the capital of the international network of Rakha Pesantren towards the development of institutions and alumni who will continue their studies to the Middle East, especially Al-Azhar University in the future. In the early days of the establishment of the Arabische School, it was an educational institution with the function of broadcasting and purifying religion. Various religious approaches were carried out with politeness, and Tuan Guru H. Abdurrasyid tried to change these deviant behaviors. On the other hand, there is a strong desire of some Muslims themselves to study Islam so that their lives are by the Qur'an and al-Sunnah and avoid heresy and cheese.